(untitled) (Journal of National Institute of Ophthalmology, 2025)
Patient satisfaction is to considered is an integral part of hospital management and quality services of healthcare system. A descriptive cross-sectional study will be conducted to understand the relationship between patient satisfaction and trigger factors and for this purpose data will be collected from three public tertiary hospitals (National Institute of ophthalmology & hospital, Dhaka. Government of Bangladesh allocated remarkable proportion of GDP for health and education. This effort has a positive impact on health and education sector in Bangladesh. Every year the demand of health care is increasing and health sector facing difficulties to maintaining the principle of high quality health care delivery. The objective of the study is to assess the level of satisfaction of patients attending the eye department of National institute of ophthalmology & Hospital, Dhaka medical college hospital, Rangpur medical college hospital and utilize the hospital service and determine the factors related to their satisfaction. The quantitative data has been collected from the hospital setting following a descriptive cross-sectional study method. Age, gender, education, occupation, marital status and number of visits were considered as an independent variable whereas as convenience, courtesy, care quality, pocket cost and physical environment will identify as dependent variables. Per capita income, distance from the hospital etc will consider as Confounding variables. A total 384 patients were interviewed following random sampling techniques from outdoor and inpatient department. Collected data was entered into SPSS for analysis. Appropriate statistical analysis were done here. An ethical approval was obtained from the NSU public health department. The patients were asked to evaluate the overall performance of the hospital. The majority (60.5%) said average and 39.5% said good. So we could conclude that the patient satisfaction is very important to increase the flow of patient and reduce the burden of eye related service. Quality of care, doctor and staff attitude and behavior need to improve to enhance the satisfaction level of patient. Hospital general hygiene facility also need to improve. J.Natl.Inst.Ophthalmol. 2023; 6(2):58-66